Optimalisasi Pelayanan Publik Bidang Administrasi dalam Pembayaran Tagihan Perusahaan Daerah Air Mineral (PDAM) (Studi di Kantor Pos Delivery Center Sekejati Kota Bandung) - Kirana, Cintantya Andhita Dara; Rahadian, Wafa Salsabila (Department of Public Administration, Muhammadiyah University of Makassar, 2023)
Public service is an absolute thing that happens in human social life. This makes public services one of the aspects that must be considered in governance for the purpose of creating satisfaction in the process of social interaction. One of the institutions that has not been able to provide maximum public services to the community is the Sekejati Post Office, Bandung City. The Sekejati Post Office in Bandung City provides several services to the community, one of which is the PDAM bill payment service. In the service process for paying PDAM bills, it was found that there are still service support facilities that have been unable to operate properly. This study aims to determine how to provide bill payment services for PDAM Post Office Sekejati Delivery Center Bandung City. The research process was carried out using qualitative research methods where in-depth interviews and observation methods carried out the data collection process. From the research that has been done, it was found that the obstacles that occur in the process of optimising the PDAM bill payment service at the Sekejati Post Office in Bandung City are systems that often have errors and there is a buildup of queues when one of the counter officers is unable to attend due to health reasons.